A Sustainable Growth Of Clean Energy In India: A Target 2022 - Ashish Singhal, Narendra Singh Beniwal , Ramlakhan Patel (International Journal of Modern Agriculture, 2021)
The extenuation of non-conventional global energy demands and changing environments is one of the most important ingredients in recent days. A case is about the study of sun energy acquired as clean energy by the government of India (GOI). GOI announced the various schemes for solar energy (SE) in the last decades because of the tremendous growth of solar energy aspects for the non-conventional sources with the support of central and state government. This article covered the progress of solar energy in India with major achievements. In this review article, the authors are trying to show the targets of the government of India (GOI) by 2022 and his vintage battle to set up a plant of solar or clean energy in India. This paper also emphasizes the different policies of GOI to schooling the people for creating the jobs in different projects like â€œMake in Indiaâ€. This paper projected the work of the dynamic Prime Minister of India Mr. Narendra Modi and his bravura performance to increase the targets 100 GW solar energy by 2022.